A Minireview on Brain Models Simulating Geometrical, Physical, and Biochemical Properties of the Human Brain - Bouattour, Yassine; Sautou, Valérie; Hmede, Rodayna; El Ouadhi, Youssef; Gouot, Dimitri; Chennell, Philip; Lapusta, Yuri; Chapelle, Frédéric; Lemaire, Jean-Jacques (Frontiers in Bioengineering and Biotechnology, 2022)
There is a growing body of evidences that brain surrogates will be of great interest for researchers and physicians in the medical field. They are currently mainly used for education and training purposes or to verify the appropriate functionality of medical devices. Depending on the purpose, a variety of materials have been used with specific and accurate mechanical and biophysical properties, More recently they have been used to assess the biocompatibility of implantable devices, but they are still not validated to study the migration of leaching components from devices. This minireview shows the large diversity of approaches and uses of brain phantoms, which converge punctually. All these phantoms are complementary to numeric models, which benefit, reciprocally, of their respective advances. It also suggests avenues of research for the analysis of leaching components from implantable devices.